2004
DOI: 10.1097/01.jnr.0000387513.75114.bb
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Sleep and Daytime Sleepiness in Depressed and Non-Depressed Mothers During the Early Postpartum Period

Abstract: Taiwanese mothers have identified insufficient sleep as a major manifestation of postpartum depression. Few studies have thoroughly examined the relationship between sleep and depression during the early postpartum period, however. The objectives of this study were to compare the characteristics of both the postpartum sleep and daytime sleepiness of depressed first-time mothers and of their non-depressed counterparts, and to determine the factors that significantly increased mothers' risks of being depressed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 28 publications
(33 reference statements)
3
54
2
Order By: Relevance
“…36,37 Our review of the published literature revealed a wide range of reported Cronbach α for the PSQI, with a low of 0.43 (among Japanese healthy participants) to a high of 0.85 (among German patients with insomnia). [8][9][10][11]13,[15][16][17]38 Although the statistic is not interpretable in our study (given the observed three-factor structure), we reported an overall Cronbach's α (0.57) so as to be consistent with the other studies. Several previous studies conducted among pregnant Australian and British women, 1,7 Norwegian postpartum women, 39 Australian adults, 40 and cancer patients in Greece 8 found that the removal of "sleep medication use" component improved the Cronbach's α for the PSQI.…”
Section: Discussionsupporting
confidence: 73%
“…36,37 Our review of the published literature revealed a wide range of reported Cronbach α for the PSQI, with a low of 0.43 (among Japanese healthy participants) to a high of 0.85 (among German patients with insomnia). [8][9][10][11]13,[15][16][17]38 Although the statistic is not interpretable in our study (given the observed three-factor structure), we reported an overall Cronbach's α (0.57) so as to be consistent with the other studies. Several previous studies conducted among pregnant Australian and British women, 1,7 Norwegian postpartum women, 39 Australian adults, 40 and cancer patients in Greece 8 found that the removal of "sleep medication use" component improved the Cronbach's α for the PSQI.…”
Section: Discussionsupporting
confidence: 73%
“…These reports also revealed a positive association with depressive symptoms and altered sleep [24,45] . With the exception of WASO, however, our findings did not show a statistically significant difference in the sleep measurements when comparing women based on our a priori cut-off for high or lowdepressive symptoms.…”
Section: Discussionmentioning
confidence: 69%
“…The postpartum women were classified as poor sleepers during the early postpartum period. The mothers reported approximately 3 hours of sleep each night 6 . Postpartum mothers with self-reports of poor sleep quality had a low perceived ability to cope with motherhood-related issues.…”
Section: Discussionmentioning
confidence: 99%